Effects of combined ultrasonic and microwave vacuum drying on drying characteristics and physicochemical properties of Tremella fuciformis - Xu, Jingxin; Wang, Danni; Lei, Yanping; Cheng, Lujie; Zhuang, Weijing; Tian, Yuting (Ultrasonics sonochemistry, 2022)
•Air-borne ultrasonic treatment was combined with microwave vacuum drying (USMVD).•USMVD affected the structure of Tremella fuciformis polysaccharides (TFPs).•USMVD-TFPs at 0.42 W/mL retained high levels of total and reducing sugar and uronic acid.•TFP samples from USMVD and US + MVD had reduced molecular weight to a certain extent.•USMVD-TFPs at 0.42 W/mL produced better viscosities and shear thinning ability in TFPs. This study analyzes the effects of ultrasonic waves on the drying kinetics of Tremella fuciformis during microwave vacuum drying. The physicochemical properties and structural characteristics of T. fuciformis polysaccharides (TFPs) were studied by drying tremella samples using hot air drying (HAD), microwave vacuum drying, ultrasonic pretreatments with microwave vacuum drying (US + MVD), and air-borne ultrasonic pretreatments combined with microwave vacuum drying (USMVD) under acoustic energy densities of 0.14, 0.28, and 0.42 W/mL. The results showed that USMVD and US + MVD accelerated the mass transfer process of T. fuciformis. Compared with HAD treatment, TFP samples obtained by USMVD and US + MVD had a reduced molecular weight to a certain extent, and they had stronger shear thinning ability. In addition, USMVD-TFPs at 0.42 W/mL retained higher total sugar, reducing sugar, and uronic acid, and the degree of reduction in the monosaccharide component content was small.